Copper bismuth oxide (CuBi2O4): Synthesis, properties and potential applications - Imam, Saifullahi (Journal of Composites and Compounds, 2025)
CuBi2O4 is a p-type semiconductor which is an outstanding representative of the spinel-type compounds. In the present article, various methods used for the synthesis of CuBi2O4 such as hydrothermal, co-precipitation, microwave-assisted, mechanochemical, solid-state etc. with the feature(s) of the product obtained have been summarized. Also, the studies reviewed have revealed that CuBi2O4 has been used as a photocatalyst, as a photocathode material, in gas sensing applications, in activating certain oxidants such as Peroxymonosulfate and H2O2, and for various other applications.